Sociorobot World A Guided Tour for All - Tzafestas, Spyros (Intelligent Systems, Control and Automation: Science and Engineering, 2016)
This book makes a consolidated guided tour to the world of sociorobots (social or socialized robots). Sociorobots and assistive robots provide entertainment, assistance to the handicapped, companionship to the elderly, and health care to autistic children and people with dementia among others. The book provides, in a fluent educational way, all major concepts, architectures, and design methodologies. All types of sociorobots are examined, namely walking anthropomorphic, wheeled anthropomorphic, fixed-place anthropomorphic, and zoomorphic sociorobots. The book provides an outline of sociorobot intelligent control architectures, robot learning, and human robot interaction.